Theories of counseling and psychotherapy : a case approach - Murdock, Nancy L. (The Merrill counseling series, 2013)
Examining the historical roots, evaluations, and lasting effects of Existential, Gestalt, Behavior, Cognitive, Reality, Feminist, Family, Narrative, and Solution-Focused Therapy and much more, Theories of Counseling and Psychotherapy: A Case Approach, 3e equips students with the history and application necessary to bring theory to life